2017
DOI: 10.1002/pc.24648
|View full text |Cite
|
Sign up to set email alerts
|

Polymer electrolyte developed from natural rubber‐polyacrylic acid co trimethoxysilyl propyl methacrylate grafted fumed silica and its application to dye sensitized solar cell

Abstract: This research focused on an electrical improvement of polymer nanocomposite which had potential for application in dye sensitized solar cells (DSSCs). This composite polymer electrolyte can be prepared by admicellar polymerization to form a core-shell structure. The shell was prepared by acrylic acid (AA) monomer copolymerization with modified silica from trimethoxysilyl propyl methacrylate monomer (MPS) and hydrophilic silica (R200) (MPS-SiO 2 ) and then coated on natural rubber (NR) as a core (PAA-adp-NR co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In 2019, the consumption of fumed silica in the silicone rubber industry accounted for more than 58% of the total consumption. In recent years, because photovoltaics, anti-impact structures, vibration isolators, adhesives, colloidal batteries, and other downstream industrial , applications are flourishing, China’s fumed silica industry is booming, and the production capacity has increased significantly. China has gradually become a major driving force for the growth of the fumed silica market globally.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the consumption of fumed silica in the silicone rubber industry accounted for more than 58% of the total consumption. In recent years, because photovoltaics, anti-impact structures, vibration isolators, adhesives, colloidal batteries, and other downstream industrial , applications are flourishing, China’s fumed silica industry is booming, and the production capacity has increased significantly. China has gradually become a major driving force for the growth of the fumed silica market globally.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in many studies, it was shown that polar functional compounds can modify the conductivity properties of NR for use in polymer electrolytes. [ 95 ] By having these abilities, NR polymer has risen as one of the polymers used in fabrication of polymer electrolytes for high‐performing energy storage devices.…”
Section: Importance Of Nr Electrolytes and Electrodes In Energy Stora...mentioning
confidence: 99%
“…Grafting of one or two molecules with NR is another method of modification in NR. [8] The reaction of olefinic double bond by addition or substitution method results in highly durable material for a variety of applications. [9][10][11] Surface tackiness and frictional resistance of NR can be overcome by this method of chemical modification.…”
Section: Introductionmentioning
confidence: 99%